Uniformidade de irrigação em sistema de gotejamento na produção orgânica de amora preta - Souza , Juciley Lima de (2022)
The efficiency of water application in the cultivation of blackberries is necessary for the period of scarcity of rain. Thus, the irrigation activity in Brazil is increasing more and more with the expansion of irrigated areas. For this purpose, the evaluation of the irrigation system is a necessary process for the good performance of the irrigation system. Therefore, it is possible to express how irrigation is being operated from the water distribution coefficients. The objective of the present work was to evaluate the uniformity of water distribution using control charts and process capability indices in a drip irrigation system in the organic production of blackberry in the municipality of Cascavel (PR). The study was carried out on a rural property located 20 km south of the municipality of Cascavel. Tests of water distribution uniformity in the drip system were performed based on the methodology proposed by Keller and Karmeli (1975). With the collected samples, Christiansen uniformity coefficients (CUC) were calculated; coefficient of uniformity of distribution (CUD); statistical uniformity coefficient (CUE); Hart's uniformity coefficient (CUH); Coefficient of Variation (CV), and application efficiency (Ea). Then, the Shewhart control charts and process capability index histograms were made. The analysis results of the CUC, CUD, CUE, and CUH coefficients showed ratings as reasonable, good, reasonable, and good, respectively. On the other hand, the coefficient of variation (CV) and application efficiency (Ea) presented improper classification. The analyses carried out with the Shewhart control charts for the irrigation uniformity coefficients proved efficient in temporal monitoring data variability in the field. The results of the potential capacity of the process (Cp) and the effective capacity of the process (Cpk) for the irrigation coefficients revealed that the drip irrigation system is not capable, indicating that the irrigation system needs to employ new water management techniques to increase irrigation quality and irrigation system performance.